Reconstruction of the Legal Framework for Consumer Protection in ESG-Based Digital Investment and Blockchain Technology: A Legal Study - Muchammad Shidqon Prabowo; Dewi Sulistianingsih; Nasarudin Abdul Rahman; Takwim Azami (Lex Scientia Law Review, 2026)
This study analyzes the regulatory framework for consumer protection in digital investment based on ESG principles and blockchain technology in Indonesia. The method used is juridical-normative with a statutory, conceptual, and comparative approach. The results of the study indicate a significant regulatory gap, including the non-recognition of the legality of smart contracts, the absence of a digital ESG claim verification mechanism, the absence of a blockchain-based dispute resolution model, and the fragmentation of supervision coordination between national authorities. As a contribution, this study offers a new legal framework model that integrates the recognition of smart contracts, the establishment of a digital ESG verification institution, the development of blockchain-based ADR, and regulatory harmonization. This innovation is expected to strengthen consumer protection in the sustainable investment ecosystem based on blockchain technology. In practice, this study recommends the formulation of the Digital and ESG Consumer Protection Law, the establishment of an independent ESG verification institution, and strengthening regulatory coordination in Indonesia. The novelty of this article is its focus on three areas of analysis: ESG, blockchain, and consumer protection. All three are analyzed from a legal perspective. The limitation of this study is the absence of empirical data; future research is recommended to use a quantitative or mix-method approach to evaluate consumer behavior in the ESG blockchain platform.